Bending two-dimensional Cu(i)-based coordination networks to inverse electrocatalytic HER/CO2RR selectivity - Zheng, Kai; Ding-Yi, Hu; Xue-Wen, Zhang; Xian-Xian Xiao; Zi-Jun, Liang; Jun-Xi, Wu; Duo-Yu, Lin; Lin-Ling, Zhuo; Heng, Yi; Gong, Li; Dong-Dong, Zhou; Jie-Peng, Zhang (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
Two-dimensional (2D) coordination polymers have attracted great attention for catalysis because of their abundant exposed active sites. Here, we show that bending the local structure of 2D coordination polymers can inverse the electrocatalytic selectivity. A series of ultrathin nanosheets based on isoreticular/isostructural/isomeric 2D Cu(i) triazolate coordination polymers were successfully prepared. By introducing an amino group on the triazolate ligand, the shape of the 2D layer transforms from planar into wavy, which inverses the electrocatalytic selectivity from the HER (selectivity ∼ 80%) to the CO2RR (selectivity ∼ 76%, C2H4 up to 52%). Computational simulations showed that the wavy structure allows the amino groups to form attractive hydrogen-bonding interactions with the key reaction intermediates of the CO2RR for C2H4 and steric hindrance with the key reaction intermediates of the HER, giving lower and higher reaction energy barriers, respectively.